The Protective Effects of Levo-Tetrahydropalmatine on ConA-Induced Liver Injury Are via TRAF6/JNK Signaling - Yu, Qiang; Liu, Tong; Li, Sainan; Feng, Jiao; Wu, Liwei; Wang, Wenwen; Chen, Kan; Xia, Yujing; Niu, Peiqin; Xu, Ling; Wang, Fan; Dai, Weiqi; et al. (Mediators of Inflammation, 2018)
Aims. Levo-tetrahydropalmatine (L-THP) is an active ingredient of Corydalis yanhusuo W. T. Wang, which has many bioactive properties. Herein, we investigated the protective effects of L-THP on concanavalin A- (ConA-) induced hepatitis in mice and explored its possible mechanisms of these effects. Main Methods. Balb/c mice were intravenously injected with 25 mg/kg ConA to generate a model of acute autoimmune hepatitis, and L-THP (20 or 40 mg/kg) was administered orally once daily for 5 d before the ConA injection. The liver enzyme levels, proinflammatory cytokine levels, and other marker protein levels were determined 2, 8, and 24 h after ConA injection. Results. L-THP could decrease serum liver enzymes and pathological damage by reducing the release of inflammatory factors like IL-6 and TNF-α. The results of Western Blot and PCR indicated that L-THP could ameliorate liver cell apoptosis and autophagy. L-THP could suppress T lymphocyte proliferation and the production of TNF-α and IL-6 induced by ConA in a dose-dependent manner in vitro. Additionally, the protective functions of L-THP depended on downregulating TRAF6/JNK signaling. Conclusion. The present study indicated that L-THP attenuated acute liver injury in ConA-induced autoimmune hepatitis by inhibiting apoptosis and autophagy via the TRAF6/JNK pathway.